Mixed Lactiplantibacillus plantarum strains alleviated DSS-induced intestinal inflammation of Balb/c mice via the 5-HT/5-HT7R/NF-κB signaling pathway. (March 2023) - Wang, Arong; Li, Panpan; Ma, Fenglian; Li, Xinling; Mu, Guangqing; Tuo, Yanfeng
Graphical abstract: Highlights: Mixed Lactobacillus intervention prevents ulcerative colitis by regulating tryptophan metabolism and increasing serotonin levels. Mixed Lactobacillus increased the expression of 5-HT7 R and inhibited the activation of NF-κB signaling pathway. We speculate that mixed Lactobacillus alleviates ulcerative colitis through the 5-HT/5-HT7 R/NF-κB signaling pathway. Abstract: In this study, single and mixed Lactobacillus strains were orally administered to Balb/c mice with colitis induced by DSS to investigate the difference in anti-inflammatory activity between single and mixed Lactobacillus strains. Our data showed that the mixed Lactobacillus strains intervention significantly ameliorated the intestinal barrier disruption and colonic inflammation in the DSS-treated mice. Furthermore, mixed  Lactobacillus  strains intervention could alleviate intestinal flora dysbiosis of the mice. By measuring the fecal metabolites of the mice, Lactobacillus  strains were found to significantly affect linoleic acid and tryptophan metabolisms. Surprisingly, the single or mixed Lactobacillus significantly upregulated fecal serotonin levels and the serotonin-related mRNA expression in colon tissue. Therefore, we deduced that the mixed Lactobacillus strains could alleviate intestinal inflammation by recovering the intestinal flora dysbiosis, increasing serotonin expression, and activating the 5-HT7 R and 5-HT4 R, which would provide a new idea to assess the ameliorating effect of probiotic strains on inflammatory bowel disease.